Urbanization and Changes in Social Structure Post-Disaster in Palu City - Abu, Ardillah; Hasriani, Hasriani; Alhabsyi, Firdiansyah (IAIN Madura, 2024)
Post-disaster urbanization in Palu City, triggered by the earthquake, tsunami, and liquefaction in 2018, has significantly impacted the social structure of the community. This study aims to analyze the phenomenon of urbanization and its effects on changes in social class, family patterns, and social solidarity in Palu City, using Auguste Comte's positivistic perspective. A descriptive qualitative approach was employed in this research, with data collected through interviews, field observations, and documentation from primary and secondary sources. The findings reveal that post-disaster urbanization has intensified social class disparities, triggered transformations in family and community structures, and led to a decline in social solidarity within urban environments. These results support Comte's view that society evolves towards a more modern and rational social structure after a disaster, with key roles played by social institutions such as the government and the economic sector. In conclusion, by objectively understanding these dynamics, more effective policies can be designed to manage urbanization processes and mitigate their negative impacts.